How political parties mobilize religion: lessons from Mexico and Turkey - Mantilla, Luis Felipe (Religious engagement in democratic politics, 2021)
"Analyzes and compares the contentious evolution of religious political parties in Mexico and Turkey, two rising regional powers with deeply rooted secularist traditions"--